Characterization of flying ashes of a thermoelectric plant for its possible use as an additive in the manufacture of cement (2017)
The results of the characterization of ‘Flying Ashes’, FA, a product of coal burning are shown in this paper. The ‘flying ashes’ samples were produced in the thermal station Termopaipa IV, in the State of Boyacá, Colombia. The techniques used for the characterization were: X-Ray Fluorescence, X-ray diffraction, Optical Microscopy (Polished Thin Section) and Electronic Microscopy. It is noticeable that the ashes are made up of aluminum and silicon compounds. Besides, iron phases in low content such as hematite and limonite were also found. Additionally, the morphology reveals presence of coke unburned coal and spheres of different size and composition. According to the features found in this study, such as: chemical and mineralogical composition, and surface characteristics have determined that the FA is an artificial pozzolanic material with acidic properties, which influences the reactivity of the ashes that is based on the chemical aspect of the lime fixing and fulfil the requirements in a high degree according to the standard for use in the cement industry.